O07.4 Incidence of sexual behaviors and relationship to the urethral microbiota among men who have sex with men (MSM) in seattle. (14th July 2019) - Chambers, Laura; Hughes, James; Fredricks, David; Srinivasan, Sujatha; Morgan, Jennifer; Hoffman, Noah; Lowens, M; Tapia, Kenneth; Glick, Sara; Khosropour, Christine; Golden, Matthew; Manhart, Lisa
Abstract : Background: Studies suggest that sexual behavior influences the composition of the male urethral microbiota, but this hypothesis has not been tested. Methods: From 12/2014–5/2018, we enrolled MSM with NGU attending an STD clinic into a cohort study. Men attended five in-clinic visits at 3-week intervals, collected weekly urine specimens at home, and reported daily antibiotics and sex on weekly diaries. We applied broad-range 16S rRNA gene PCR with deep sequencing to urine. We estimated incidence of insertive oral sex (IOS) only, condomless insertive anal intercourse (CIAI) only, and IOS with CIAI (IOS+CIAI) after NGU diagnosis using Poisson regression with robust standard errors. We estimated the association between urethral sexual exposures (referent group=none) in seven 3-day time windows before specimen collection and Shannon Index (diversity) and log10 number of bacterial species (richness) using generalized estimating equations, adjusting for recent antibiotics, age, race/ethnicity, HIV status, and PrEP use. For each exposure category, we tested whether all seven window coefficients were equal to zero (i.e., no overall association) using a Wald test. Results: Among 92 MSM with NGU, median age was 31 (interquartile range [IQR]=28–40); 55% were non-Hispanic white. They contributed 1, 095 person-weeks of behavioral data (median=12 diaries/man, IQR=12–13). Incidence of any sex, IOS only, CIAI only, and IOS+CIAI were 1.07 (95% confidence interval [CI]=0.93–1.24), 0.40 (95%CI=0.32–0.49), 0.10 (95%CI=0.07–0.15), and 0.40 (95%CI=0.30–0.52) episodes per person-week, respectively. Among 894 urine specimens (median=10 specimens/man, IQR=8–12), median diversity was 1.33 (IQR=0.76–1.99), and median richness was 14 species (IQR=9–23). Overall, CIAI only ( P <0.01 in each model) but not IOS only or IOS+CIAI in the prior 21 days was associated with diversity and log10-richness. Diversity and log10-richness were lower 1–3 days after and higher 16–18 days after CIAI only. Conclusion: Among MSM after NGU, CIAI only in the prior 21 days was independently associated with diversity and richness of the urethral microbiota. Disclosure: No significant relationships.